PENGARUH EIGHT-FORMS OF MOVING MEDITATION TERHADAP PENURUNAN FATIQUE PADA PASIEN POST-HAEMODIALYSIS - Lisa Mustika Sari; Aldo Yuliano; Auliani Annisa Febri (JURNAL KESEHATAN PERINTIS, 2017)
Chronic renal failure is a major health problem in the world. The prevalence of chronic renal failure aged > 15 years in West Sumatra was 0.2% for patients with hemodialysis therapy where Bukittinggi and surrounding areas were in regional Public Hospitals Dr. Achmad Mochtar. Fatigue has a high prevalence in the population of dialysis patients to overcome the fatigue is one of them is eight- forms of moving meditation relaxation technique. The aim of research to see average pre, post and decline as well as decrease fatigue of eight- forms of moving meditation to patients post-hemodialysis at Outpatient Unit Regional Public Hospital Dr. Achmad Mochtar Bukittinggi 2016. This research was conducted on July 11- 24th, 2016. The study design using Quasi-Experimental Design, in the form of Pre-Post Test One Group Design carried out for 20-30 minutes. Samples in this study were 18 people with sampling techniques is accidental sampling. Collecting data using FAS sheet, statistical tests using test formula Paired T-Test. Collecting data using FAS sheet, statistical tests using test formula Paired T-Test. This study showed that the average pre 29.917, post 25.333 and decrease of fatigue 4.5833 in post-hemodialysis patients with p value <α (0.000 <0.05).Conclusion that giving eight-forms of moving meditation can reduce fatigue in post-hemodialysis patients. Suggested to care institution as an input in order to make the exercise of eight-forms of moving meditation as an alternative therapy for symptoms of fatigue in hemodialysis patients.